ANALISIS PROYEK PENGUATAN PROFIL PELAJAR PANCASILA DENGAN MEDIA CARD SHORT DIMENSI BERNALAR KRITIS DI KELAS IV MI AL-IMAN KRAKSAAN - Hilyatul Jannah; Choerul Anwar Badruttamam; Farich Purwanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the use of card short media in the Pancasila Student Profile (P5) strengthening project in the critical reasoning dimension in class IV MI Al-Iman Kraksaan. This research was conducted at MI Al-Iman in the 2024/2025 academic year. This study uses a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. The subjects of this study were all students of class VI MI Al-Iman. The object of this study is the Pancasila Student Profile Strengthening Project with Card Short Media in the Critical Reasoning Dimension. The results of the study show that students have been actively involved in the critical thinking process. This is evidenced by their ability to analyze information, evaluate arguments, and formulate conclusions logically. With the help of media, especially card short media, students are much more enthusiastic in the teaching and learning process so that they can help students think logically and systematically, but are constrained by variations in use, time, and teacher skills.